Silica Biomineralization of Calothrix-Dominated Biofacies from Queen's Laundry Hot-Spring, Yellowstone National Park, USA - Smythe, Wendy F.; McAllister, Sean M.; Hager, Kevin W.; Hager, Kyle R.; Tebo, Bradley M.; Moyer, Craig L. (Frontiers in Environmental Science, 2016)
Experiments on microorganisms capable of surviving silicification are often conducted to gain a better understanding of the process of silica biomineralization and to gain insights into microbially influenced rock formations and biofabrics like those found in ancient deposits such as the Early Archean Apex Chert formation (House et al., 2000; Schopf, 1993). An ideal microorganism for studying silicification is the large sheathed cyanobacterium Calothrix, which form distinctive organo-sedimentary structures in the low to moderate temperature regions of hydrothermal springs or columnar stromatolitic structures in aquatic systems. Our ability to identify and characterize microfossils from ancient deposits allows us to gain a better understanding of environmental conditions on early Earth. Here we characterized Calothrix-dominated biofacies along the outflow apron of Queen’s Laundry Hot-Spring in Yellowstone National Park using microscopy and molecular techniques to examine biofacies morphology and phylogenetic diversity. We found that flow regime and temperature had a profound effect on community composition as identified by the observation of five distinct Calothrix-dominated communities and on biofacies architecture along the outflow apron.